1998
DOI: 10.1152/ajpheart.1998.275.6.h2334
|View full text |Cite
|
Sign up to set email alerts
|

Chronic circadian desynchronization decreases the survival of animals with cardiomyopathic heart disease

Abstract: Shift work is associated with increased cardiovascular morbidity and mortality. Whereas it has been suggested that continuous shifting of the circadian clock/sleep-wake cycle may have negative effects on health, there is very little experimental evidence to support such a hypothesis. Cardiomyopathic Syrian hamsters were either maintained on a fixed light-dark (LD) cycle ( n = 31) or were subjected to a 12-h phase shift in the LD cycle on a weekly basis ( n = 32). The duration of the life span was recorded for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 19 publications
4
120
0
2
Order By: Relevance
“…It has been proposed that GCs are one of the pathways by which the SCN synchronizes the peripheral oscillators (Le Minh et al 2001). This is critically important for organizing the metabolism of the whole body (Penev et al 1998). The findings of the present study may thus be useful for further investigations on this topic.…”
Section: Glucose Tolerance Testmentioning
confidence: 53%
“…It has been proposed that GCs are one of the pathways by which the SCN synchronizes the peripheral oscillators (Le Minh et al 2001). This is critically important for organizing the metabolism of the whole body (Penev et al 1998). The findings of the present study may thus be useful for further investigations on this topic.…”
Section: Glucose Tolerance Testmentioning
confidence: 53%
“…Whether meals scheduled at abnormal circadian times, as occurs during shift work, also leads to such ''internal desynchronization'' in humans has yet to be determined. In some animal models, repeated shifts in the light/dark cycle-typical of shift workleads to premature death, while mutations of circadian clock genes can lead to signs of metabolic syndrome (11,26,27), supporting the potential negative health consequences of circadian disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, shift work has been linked to increased BMI and higher rates of gastrointestinal disorders, cardiovascular disease, as well as diabetes [36]. Few animal models of ''shift work'' have been developed, but one provocative study demonstrated that reversing the light:dark cycle on a weekly basis hastened death in cardiomyopathic hamsters, suggesting that circadian desynchronization may have exacerbated and complicated the pre-disposed disease state in these animals [37].…”
Section: The Circadian Clock: External and Internal Synchronizationmentioning
confidence: 99%